Penerapan Statistik Deskriptif pada Pengembangan Sistem Informasi SMART RT/RW untuk Peningkatan Pelayanan Kepada Masyarakat - Arif Prasetiyo Utomo; Anjik Sukmaaji; Agus Dwi Churniawan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
The Smart RT RW Information System is an application designed with the aim of providing financial statement information and citizen services in one reach. This Smart RT RW Information System has features that are tailored to the identified problems, namely the lack of transparency in financial management, manual reception records and lack of efficiency in administrative services. Based on the existing problems, the solution given is to design a Smart RT RW Information System Using a Website-Based Descriptive Statistical Method at Pakal Residence Housing Surabaya. This descriptive statistical method is concerned with collecting and presenting a data set so that it can provide useful information. This descriptive statistical method is used to present data on population information, financial reports of residents, visiting guests, and administrative services. The test results of the Smart RT RW application using blackbox testing were completely successful because based on the results of the trial this application helped residents to see payment of fees, monitor visiting guests, help process computerized correspondence, manage distribution of social assistance and assist residents in expressing aspirations.